The well-being of Sámi children and the realisation of their rights - Weckström, Elina; Kekkonen, Karri; Kekkonen, Outi (fi=Lapsiasiavaltuutetun toimisto|sv=Barnombudsmannens byrå|en=Office of the Ombudsman for Children|, 2023)
The survey was carried out in 2022 by the Office of the Ombudsman for Children as part of the National Child Strategy. It was taken by children aged 11–17 who identify as Sámi, both from the Sámi Homeland and other parts of Finland. Six children were interviewed for the electronic questionnaire, which was taken by 83 children.